2017
DOI: 10.1371/journal.pone.0187561
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress inhibits expression of genes involved in thyroid hormone synthesis and their key transcriptional regulators in FRTL-5 thyrocytes

Abstract: Endoplasmic reticulum (ER) stress is characterized by the accumulation of misfolded proteins due to an impairment of ER quality control pathways leading to the activation of a defense system, called unfolded protein response (UPR). While thyrocytes are supposed to be highly susceptible to environmental conditions that cause ER stress due to the synthesis of large amounts of secretory proteins required for thyroid hormone synthesis, systematic investigations on the effect of ER stress on expression of key genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…FRTL-5 thyrocytes treated with tunicamycin, an ER stress inducer, showed increased levels of XBP1 and other UPR molecules but also showed a reduction in thyroid hormone synthesis. This indicates the role of ER stress-activated molecules in thyroid hormone synthesis ( 319 ). However, IRE1α has not been studied extensively in this disease.…”
Section: Ire1α Involvement In Autoimmune and Inflammatory Diseasesmentioning
confidence: 89%
“…FRTL-5 thyrocytes treated with tunicamycin, an ER stress inducer, showed increased levels of XBP1 and other UPR molecules but also showed a reduction in thyroid hormone synthesis. This indicates the role of ER stress-activated molecules in thyroid hormone synthesis ( 319 ). However, IRE1α has not been studied extensively in this disease.…”
Section: Ire1α Involvement In Autoimmune and Inflammatory Diseasesmentioning
confidence: 89%
“…Thus perhaps these responses are to be expected, yet to us it is particularly notable that along with decreased levels of phospho-S6-kinase, thyrocytes adapted to chronic continuous ER stress maintain a lower overall protein synthesis level while exhibiting a growth rate that ultimately is comparable to that of unstressed cells. To us, this suggests the likelihood that protein synthesis machinery is less directed to proteins representing thyroid differentiated function (40) while preserving those proteins needed for continued cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…As Tg is the major secretory glycoprotein of thyrocytes, the disturbance of the thyrocytes ER homeostasis could interfere with the folding of Tg. Wen et al (39) reported that TM-treated FRTL-5 cells resulted in ER stress and the decrease of Tg protein, although the authors suggested the decreased mRNA level might be responsible. Other research using thapsigargintreated FRTL-5 cells revealed the block of Tg secretion, with the disturbance of Tg folding and retention in the ER (18).…”
Section: Discussionmentioning
confidence: 99%